When, where and why we use the mobile app? A study on the use contexts for the mobile app - Aihua Zhang; Junwan Yin; Bo Yuan; Ying Kong (International Telecommunications Society (ITS), 2017)
Mobile APP develops very rapidly, while, different from some fixed contexts using traditional products, people can use the mobile applications anytime, anywhere. This paper combined the reference literature with the current situation of APP market, built a model of using mobile APP named "context-APP-gratification”. Referred to context, referring to relevant literature, the contexts of using mobile APPs are divided into 7 categories by the two-step clustering: the "family leisure group", the "outdoor activity group" and the "office work group". Referred to gratification, five types of gratification using mobile APPs are summarized by using the grounded theory in the pilot study and verified by factor analysis in the main study. In a further study, the relationships among the contexts of APPs, the types of APPs, and the gratifications of APPs are studied. In addition, for different types of APP, this paper also propose management recommendations combined with the market analysis.
Keywords: 330; Context; APP; Uses and gratifications